Comparative Study of Prevalence of Pterygium at High Altitude and Kathmandu Valley - Shrestha, S; Shrestha, S M (Journal of Nepal Health Research Council, 2015)
Background: Pterygium is a fleshy fibrovascular growth of conjunctiva encroaching upon the superficial cornea towards the visual axis in the nterpalpebral fissure. The study aims to compare the prevalence of pterygium at high altitude and Kathmandu. Methods: A cross sectional quantitative study organized by Professional Support Service Nepal was conducted at Mustang and Kathmandu Valley in the Tibetan and Thakali population. The sample size at Mustang is 222 and Kathmandu Valley is 186. Results: At Mustang, pterygium was present in 40 males (38.5%) and 48 females (40.7%) while at Kathmandu,pterygium was present in 6 males (8.8%) and 17 females (14.4%). Pterygium was present in 20.7% (n=12) at the altitude of 2710 meters, 28.8% (n=21) at an altitude of 2900 meters, 56.6% (n=30) at 3500 meters and 65.8% (n=25) at 3800 meters. The prevalence of Pterygium was significantly high with the rise in altitude (p value=0.000). Pterygium was present in 12.4% (n=23) at Kathmandu.The prevalence of pterygium at high altitude as compared with Kathmandu was also statistically significant (p value = 0.000).Pterygium was present in <40years in 40% and =/>40years in 39.5% at high altitude. At Kathmandu,pterygium was present in <40years in 8.2% and=/> 40years in 13.9%.At Mustang, among participants with the duration of stay at high altitude up to 20 years, pterygium was present in 36.1% (n=13) and those with >20years, pterygium was present in 40.3%(n=75). Conclusions: Pterygium has significantly higher prevalence at high altitude as compared to lower altitude. Keywords: high altitude; prevalence; pterygium; Kathmandu.